KEBIJAKAN KEPALA SEKOLAH DALAM IMPLEMENTASI KURIKULUM MERDEKA DI SEKOLAH MENENGAH KEJURUAN YADIKA KOTA JAMBI - Risma Fitri; Samsu; Fridiyanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study explores the policy and practice of implementing the Merdeka Curriculum at SMK Yadika Jambi from the headmaster’s perspective. A qualitative research design was used, with data collected through interviews, observations, and documentation; data analysis followed the stages of reduction, presentation, and conclusion drawing. The results indicate that the implementation of the Merdeka Curriculum involved several key policies: teachers and the headmaster are required to use the Merdeka Mengajar Platform (PMM) for self-learning; participation in webinars; formation of teacher learning communities; development and use of curriculum-aligned teaching materials with guidance from reliable resource persons; and mechanisms for evaluation and student assessment. However, implementation also faces challenges such as teachers’ limited skills in using learning media and insufficient facilities and infrastructure. For student evaluation, the headmaster applies a combination of data collection, interviews and discussions, project/activity-based assessments, written tests, and teacher collaboration. These findings illustrate concrete efforts to translate the Merdeka Curriculum policy into classroom practice, while also highlighting the need for adequate infrastructure and teacher training to optimize implementation.